2016
DOI: 10.1016/bs.irn.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Painful Diabetic Neuropathy

Abstract: Pain-sensing sensory neurons (nociceptors) of the dorsal root ganglia (DRG) and dorsal horn (DH) can become sensitized (hyperexcitable) in response to pathological conditions such as diabetes, which in turn may lead to the development of painful peripheral diabetic neuropathy (PDN). Because of incomplete knowledge about the mechanisms underlying painful PDN, current treatment for painful PDN has been limited to somewhat non-specific systemic drugs that have significant side effects or potential for abuse. Rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 51 publications
1
7
0
1
Order By: Relevance
“…Although current medication for PDN is unsatisfactory or has significant side effects [3], the potential value of electroacupuncture, which is widely used in pain management nowadays, in treating PDN has begun to attract attention [20,21]. Accumulating evidence demonstrated that electroacupuncture (EA) at low frequency could effectively attenuate neuropathic pain [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although current medication for PDN is unsatisfactory or has significant side effects [3], the potential value of electroacupuncture, which is widely used in pain management nowadays, in treating PDN has begun to attract attention [20,21]. Accumulating evidence demonstrated that electroacupuncture (EA) at low frequency could effectively attenuate neuropathic pain [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with PDN often experience aberrant pain sensation, including spontaneous pain, hyperalgesia, and allodynia that seriously affect their life quality [2]. Studies show that several ion channels and receptors in dorsal root ganglia (DRG) are dysregulated in PDN, which make a contribution to sensitization of pain responses by enhancing excitability of nociceptor [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…For example, patients with diabetic neuropathy whose pain is driven by spinal disinhibition will demonstrate impaired RDD and may respond preferentially to anti-neuropathic pain medications that overcome disinhibition such as SNRI’s [115, 114]. Conversely patients with pain driven predominantly by peripheral mechanisms such as nociceptor hyperexcitability might show greater therapeutic response to drugs acting on ion channels of primary afferents [128]. Using RDD as a simple to employ biomarker may also be useful to select patients likely to be most responsive to a given therapy undergoing clinical trial based on the primary mechanism of pain generation.…”
Section: Discussionmentioning
confidence: 99%
“…DN is the most frequent complication of DM and finally contributes to the increase of morbidity and mortality. [1] It includes peripheral neuropathy, single neuropathy, and autonomic neuropathy, which mainly affects the distal end of the lower extremities, often characterized by loss of sensation, pain, numbness, gait disorder even amputation. Despite a high prevalence rate, the pathological mechanism of DN remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…[2,3] Early detection of DN can only be achieved by assessing the nerve fibers, and current treatment of DN is limited to certain non-specific drugs with side effects and possibility of abuse. [1,4] DN has a significant impact on the health-related quality of life.…”
Section: Introductionmentioning
confidence: 99%